0599 An aptamer-based biosensor for detection of aflatoxin M1. (1st October 2016) - Guo, X.; Wen, F.; Zheng, N.; Li, S.; Fauconnier, M. L.; Wang, J.
Abstract: Aflatoxin M1 (AFM1 ), one of the most toxic mycotoxins, imposes serious health hazards. AFM1 had previously been classified as a group 2B carcinogen and has been classified as a group 1 carcinogen by the International Agency for Research on Cancer (IARC) of the World Health Organization (WHO). Determination of AFM1 thus plays an important role for quality control of food safety. In this work, a sensitive and reliable aptasensor was developed for the detection of AFM1 . The immobilization of aptamer through a strong interaction with biotin-streptavidin was used as a molecular recognition element, and its complementary ssDNA was employed as the template for real-time quantitative polymerase chain reaction (RT-qPCR) amplification. Under optimized assay conditions, a linear relationship (ranging from 1.0 × 10 −4 to 1.0 µg L −1 ) was achieved with a limit of detection (LOD) down to 0.03 ng L −1 . In addition, the aptasensor developed here exhibits high selectivity for AFM1 over other mycotoxins and small effects from cross-reaction with structural analogs. The method proposed here has been successfully applied to quantitative determination of AFM1 in infant rice cereal and infant milk powder samples. Results demonstrated that the current approach is potentially useful for food safety analysis, and it could be extended to a large number of targets.